Pengaruh pemberian mata kuliah kewirausahaan terhadap minat wirausaha pada mahasiswa diploma 4 rekognisi pembelajaran lampu teknik listrik bandara 2A politeknik penerbangan indonesia curug - Harits Prabowo Nuryadin; Ewananda Rakadifa; Fajar Hamzah; Fuji Ismatul Rahma; Iqbal Fakar Anwara; Feti Fatonah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to determine the influence of Entrepreneurship courses on the entrepreneurial interest of Diploma IV Recognition of Prior Learning (RPL) students in the Airport Electrical Engineering (TLB) 2A class at the Indonesian Civil Aviation Polytechnic of Curug. The research employed a descriptive qualitative method, involving 20 students who had completed the Entrepreneurship course. Data were collected through questionnaires and interviews to explore students’ understanding, motivation, attitudes, and interest in entrepreneurship after participating in the course.The results indicate that the Entrepreneurship course positively affects students’ entrepreneurial interest. Most respondents (70%) expressed a desire to start a business within the next one to two years, while others planned to do so after graduation or were still developing business ideas. The main driving factors include increased understanding of business concepts, improved creativity, self-confidence, and enhanced risk-taking ability. In addition, the course encouraged students to identify business opportunities relevant to their technical background in airport electrical engineering. However, limited capital, lack of practical experience, and fear of failure remain the primary obstacles to starting a business.Overall, the Entrepreneurship course has proven effective in fostering students’ enthusiasm, entrepreneurial mindset, independence, and readiness to become innovative, responsible, and ethical young entrepreneurs who are capable of creating employment opportunities in the future.